1996
DOI: 10.1289/ehp.961041180
|View full text |Cite
|
Sign up to set email alerts
|

Latex allergens in tire dust and airborne particles.

Abstract: The prevalence and Severity of l ailergy has increased matically in the last 15

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(16 citation statements)
references
References 42 publications
(37 reference statements)
0
16
0
Order By: Relevance
“…[29][30][31] Heavy vehicles, as a major source of tyre debris in the sediment and of tyre dust in suspended particulate, could be directly responsible of latex allergy. 32 Stronger associations were found for children reporting severe asthmatic and bronchitic symptoms in the year before interview (table 4). This finding may simply reflect a better clinical specificity of the groups (less false positive subjects included), but also could be interpreted as confirmation of an increased susceptibility of the sicker children to environmental pollution.…”
Section: Interpretation Of Resultsmentioning
confidence: 94%
“…[29][30][31] Heavy vehicles, as a major source of tyre debris in the sediment and of tyre dust in suspended particulate, could be directly responsible of latex allergy. 32 Stronger associations were found for children reporting severe asthmatic and bronchitic symptoms in the year before interview (table 4). This finding may simply reflect a better clinical specificity of the groups (less false positive subjects included), but also could be interpreted as confirmation of an increased susceptibility of the sicker children to environmental pollution.…”
Section: Interpretation Of Resultsmentioning
confidence: 94%
“…11 Another more subtle effect of tire wear on human health may be the presence of latex allergens. 12 A recent epidemiological study revealed contemporaneous linear correlations between asthma mortality rates and radial-tire use, rather than with other traffic-related factors. 13 More recently, evidence that organic extracts from tire rubber can cause localized damage to the plasma membrane of human lung epithelial cells has been reported.…”
Section: ' Introductionmentioning
confidence: 99%
“…The samples, except for the pine-smoke, were extracted three times under ultrasonic agitation, 30 min each with 40 mL of a 2:1 mixture of dichloromethane (DCM) and methanol (MeOH). Smoke from the combustion of pine-needles and branches retained on a glass thimble was Soxhlet extracted with DCM/MeOH (95:5) for 24 h. Before extraction, the samples were spiked with a mixture of deuterated surrogates (i.e., octadecanoic acid-d 35 for the resin acids, and naphthalene-d 8 , anthracene-d 10 , p-terphenyl-d 14 , and benz[a]anthracene-d 12 for PAHs) to correct for losses during sample preparation.…”
Section: ' Introductionmentioning
confidence: 99%
“…In fact, several reports [23,54,55,60] refer to the presence of organic components that can be leached. The TD organic fraction, obtained by extraction in soxhlet apparatus and analysed with FTIR, contained isoprene as the principal chemical compound.…”
Section: Discussionmentioning
confidence: 99%
“…PM 10 [12,13], diesel exhaust particles (DEP) [14-17] and ultrafine particles [18,19] have received attention and been extensively analysed for their cytotoxicity, while the particulate deriving by tire abrasion on the road received a consideration limited to its impact on the soil, since it releases a large amount of zinc [20], and on the ambient air for its metal composition [21,22]. Previously, the presence of latex allergens in tire dust was suggested by Miguel et al [23], who outlined that this component could be an important factor in producing latex allergies and asthma symptoms.…”
Section: Introductionmentioning
confidence: 99%